Kesan terapi praktikal ibadah Ramadhan dan rangsangan auditori menggunakan surah al Quran terpilih terhadap gangguan tidur kanak-kanak autistik / Mohd Amzari Tumiran - Mohd Amzari , Tumiran (2018)
Sleep disturbance is a common problem that occurs at all level of ages and health condition. It would lead to negative symptoms in the human nervous system. Those who are often in experiencing the negative effects of sleep disorders are autistic individuals. They usually have an abnormal sleeping patterns. Recitation of Quran is believed to be a therapy for sleep disorders either reciting or listening to it. Negative symptoms of autism are expected to deteriorate after undergoing this therapy. The objective of this study is to identify the specific sleep disorders of autistic children through midday napping and night sleep, to identify the specific chapters and verses of Quran for use as the therapy for sleep disorders, to assess the effectiveness of Quranic verses therapy to the night sleep, to assess the effectiveness using Ramadan practical deeds (fasting, performing tarawih prayers and taking pre-dawn meals) on the quality of night sleep, and to assess the appropriateness of sleeping assessment devices for autistic children. This case study involved an autistic child who has the ability in memorizing Al-Quran in specific and detailed notion, but experienced certain sleeping disturbances. The subject a male child aged 13 years old and able to perform Ramadan in a similar way to typical children. Sleep assessment devices used in this study there were wrist actigraphy (Lark Pro) and a non-contact actigraphy (Gear4 and S+). This study found that there were significant sleep disorder which was insomnia, and other disturbances involving TST (total sleep time) and sleeping at physiological levels. Quranic therapy was founded through the recitation of certain Quranic chapters and verses as recommended by the prophetic tradition. There was an improvement of sleep score and TST (total sleep time), improvement as well as the stabilization of REM (rapid eye movement), also the reduction of insomnia symptoms after undergoing the Quranic therapy. There were no significant changes found in sleep score after Ramadan therapy was applied, as well as no occurances of insomniac events and suggested there were a psychotherapeutic benefits in this therapy. S+ that acted as a non-contact sensor biomotion device was found to meet its suitability for this autistic child in assessing the night sleep and Gear4 in assessing the midday napping or qaylulah.